Identification of potassium phosphite responsive miRNAs and their targets in potato - Rey Burusco, María Florencia (2019)
Micro RNAs (miRNAs) are small single strand non-coding RNAs that regulate geneexpression at the post-transcriptional level, either by translational inhibition or mRNA degradation based on the extent of complementarity between the miRNA and its target mRNAs. Potato (Solanum tuberosum L.) is the most important horticultural crop in Argentina. Achieving an integrated control of diseases is crucial for this crop, where frequent agrochemical applications, particularly fungicides, are carried out. A promising strategy is based on promoting induced resistance through the application ofenvironmentally friendly compounds such as phosphites, inorganic salts of phosphorous acid. The use of phosphites in disease control management has provento be effective. Although the mechanisms underlying their effect remain unclear, we postulated that miRNAs could be involved. Therefore we performed next generation sequencing (NGS) in potato leaves treated and non treated with potassium phosphite (KPhi). We identified 25 miRNAs that were expressed differentially, 14 already annotated in miRBase and 11 mapped to the potato genome as potential new miRNAs. A prediction of miRNA targets showed genes related to pathogen resistance,transcription factors, and oxidative stress. We also analyzed in silico stress and phytohormone responsive cis-acting elements on differentially expressed pre miRNAs. Despite the fact that some of the differentially expressed miRNAs have been already identified, this is to our knowledge the first report identifying miRNAs responsive to abiocompatible stress resistance inducer such as potassium phosphite, in plants.Further characterization of these miRNAs and their target genes, might help toelucidate the molecular mechanisms underlying KPhi-induced resistance.